THE ASSOCIATION OF BODY MASS INDEX, BLOOD PRESSURE AND FASTING BLOOD SUGAR WITH GENDER IN THE UNITED NATIONS STAFF OF LIBERIA - Ibrahim, Muhammad Imran; Nasreen, Khalida; Kamal, Shaheen (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the association of body mass index, blood pressure and fasting blood sugar with the gender in the UN staff of Liberia.Study Design: Cross sectional study.Place and Duration of Study: Level-II Hospital Monrovia, Liberia, from May to Aug 2017.Methodology: This study was conducted in the United Nation staff of Liberia, at level-II Hospital, where, routine medical check was conducted and anthropometric measurements as well as blood pressure and fasting blood sugar values were noted. Body mass index, fasting blood sugar and blood pressure values were recorded and fasting blood sugar and blood pressure values were compared for its relationship with varying body mass index values.Result: Total 300 individuals were monitored, out of them 226 (75.3%) were males and 74 (24.7%) were females. Mean weight of males was found to be 81 ± 14.6 Kg and for females 72.5 ± 11.6 kg there was found statistically significant (p